Subsistence-settlement systems and intersite variability in the Moroiso Phase of the Early Jomon Period of Japan - Habu, Junko, 1959- (Archaeological series (Ann Arbor, Mich.), 2001)
This book examines the settlement patterns and intersite variability in lithic assemblages of Early Jomon (ca. 5000 BP) hunter-gatherers in Japan. A model is proposed that links regional settlement patterns and intersite lithic assemblage variability to residential mobility. The results of this study suggest that the Early Jomon people were not sedentary, as previously assumed, but instead moved their residential basis seasonally. The implications of this result are discussed in the context of the development of hunter-gatherer cultural complexity in general and the course of Japanese prehistory in particular.